Long‐term follow‐up of beta cell replacement therapy in 10 HIV‐infected patients with renal failure secondary to type 1 diabetes mellitus. Issue 8 (28th February 2020) - Roll, Garrett R.; Posselt, Andrew M.; Freise, Jonathan; Baird, Julia; Syed, Shareef; Mo Kang, Sang; Hirose, Ryutaro; Szot, Gregory L.; Zarinsefat, Arya; Feng, Sandy; Worner, Giulia; Sarwal, Minnie; et al.
Abstract : The approach to transplantation in human immunodeficiency virus (HIV)‐positive patients has been conservative due to fear of exacerbating an immunocompromised condition. As a result, HIV‐positive patients with diabetes were initially excluded from beta cell replacement therapy. Early reports of pancreas transplant in patients with HIV described high rates of early graft loss with limited follow‐up. We report long‐term follow‐up of islet or pancreas transplantation in HIV‐positive type 1 diabetic patients who received a kidney transplant concurrently or had previously undergone kidney transplantation. Although 4 patients developed polyoma viremia, highly active antiretroviral therapy and adequate infectious prophylaxis were successful in providing protection until CD4+ counts recovered. Coordination with HIV providers is critical to reduce the risk of rejection by minimizing drug‐drug interactions. Also, protocols for prophylaxis of opportunistic infections and strategies for monitoring and treating BK viremia are important given the degree of immunosuppression required. This series demonstrates that type 1 diabetic patients with well‐controlled HIV and renal failure can be appropriate candidates for beta cell replacement, with a low rate of infectious complications, early graft loss, and rejection, so excellent long‐term graft survival is possible. Additionally, patients with HIV and cardiovascular contraindications can undergo islet infusion. Abstract : The authors report long‐term outcomes following beta cell replacement in people with type 1 diabetes and HIV comparable to HIV uninfected recipients.